Crohn's Disease with Mesalazine Allergy that Was Difficult to Differentiate from Comorbid Ulcerative Colitis - Tsuboi, Rumiko (Intern Med, 2018)
An 18-year-old man diagnosed with ileocolonic Crohn's disease with circumferential strictures of the ascending colon started treatment with mesalazine and subsequently underwent right hemicolectomy. After surgery, the patient was started on adalimumab, and the clinical course was favorable. Nine months postoperatively, colonoscopy revealed granular mucosa with circumferential and continuous involvement from the transverse colon down to the rectum, findings which resembled ulcerative colitis. Mesalazine allergy was suspected, and the inflammatory findings resolved after discontinuing mesalazine. In patients of inflammatory bowel disease receiving mesalazine with an atypical clinical course, the possibility of mesalazine allergy must be borne in mind.